POTENTIAL TYPES OF CRICKET BAIT (Acheta domesticus) ON FISH CATCH RESULTS USING FISHING RODS IN THE SWAMP WATERS OF KAMPUNG WASUR - Lindon Pane; Sendy Lely Merly; Jeremias Rumala Tuhumena; Silas Tanggu Redu (Universitas Mataram, 2024)
The dynamics of swamp waters are developing very rapidly in terms of fulfilling the economic needs of the community to support prosperity. Fishing activities are one aspect of realizing these needs. Therefore, this research aims to find alternative fish bait in the swamp of Wasur Village, Merauke Regency, South Papua. Crickets (Acheta domesticus) were chosen as an alternative bait because they are still related to traditional bait, namely kroto. This research was conducted for three months (July-September 2023) using quantitative descriptive methods. The fishing technique used is using a fishing rod as is often used by the local community so that it is easy to adopt later. The research results showed that the two most dominant fish species caught were Climbing perch (Anabas testudineus) and Snakehead fish (Channa striata). There were 60 Climbing perch caught, while 42 snakehead fish were caught. Analysis of the relationship between length and weight shows that both fish species have negative allometric growth patterns. This means that the increase in body length of the fish is faster than the increase in weight. Crickets have been proven to be an effective alternative fish bait in the Kampung Wasur swamp.